Light-Induced Migration of Spin Defects in TiO2 Nanosystems and their Contribution to the H2 Evolution Catalysis from Water - Bad'Ura, Zdenek; Naldoni, Alberto; Qin, Shanshan; Bakandritsos, Aristides; Kment, Stepan; Schmuki, Patrik; Zoppellaro, Giorgio (Chemsuschem, 2021)
The photocatalytic activity for H2 production from water, without presence of hole scavengers, of thermally reduced TiO2 nanoparticles (H-500, H-700) and neat anatase were followed by in-situ continuous-wave light-induced electron paramagnetic resonance technique (CW-LEPR), in order to correlate the H2 evolution rates with the electronic fingerprints of the photoexcited systems. Under UV irradiation, photoexcited electrons moved from the deep lattice towards the superficially exposed Ti sites. These photogenerated redox sites mediated (e−+h+) recombination and were the crucial electronic factor affecting catalysis. In the best-performant system (H-500), a synergic combination of mobile electrons was observed, which dynamically created diverse types of Ti3+ sites, including interstitial Ti3+, and singly ionized electrons trapped in oxygen vacancies (VO.). The interplay of these species fed successfully surface exposed Ti4+ sites, which became a catalytically active, fast reacting Ti4+⇄Ti3+ state that was key for the H2 evolution process.
CRIS-Team Scopus Importer:2021-09-10
Keywords: EPR spectroscopy; H; photocatalysis; titanium dioxide; water splitting